Achieving low-temperature Cu–Cu bonding platform via area-selective metal films with superior surface roughness for advanced packaging - Mu-Ping Hsu; Chi-Yu Chen; Hsin-Chi Chang; Kuan-Neng Chen (Journal of Materials Research and Technology)
This study addresses the critical challenge of achieving low-temperature Cu–Cu bonding for advanced packaging applications by optimizing area-selective electroless Au passivation. We demonstrate that an Ar/N2 plasma pretreatment, applied prior to Au deposition, substantially strips oxides, renders the Cu surface amorphous and highly hydrophilic, and thus suppresses grain-boundary-selective Au displacement to form a smooth, continuous passivation layer. The resulting amorphous Cu surface layer facilitates the formation of continuous Au films without “lightning-like” patterns, enabling reliable chip-to-chip bonding at temperatures as low as 150 °C under ambient conditions. Compared to O2 or N2-only plasma treatments, the Ar/N2 approach yields stronger bonds, improved void filling by Cu diffusion, and higher electrical yields and stability. These findings underscore the importance of pretreatment engineering in electroless plating processes, paving the way for more robust, scalable, and cost-effective Cu–Cu bonding solutions in next-generation advanced packaging.